2020
DOI: 10.33393/grhta.2020.2173
|View full text |Cite
|
Sign up to set email alerts
|

AIFA time-to-reimbursement: a comparison between the last two committees from 2015 to 2020

Abstract: Objective. To compare the time-to-reimbursement of the last two committees of the Italian Medicines Agency (AIFA), respectively appointed in 2015 and in 2018. Methods. The analysis was run through a specific internal database created by MA-Provider. The database was populated with information regarding European Medicines Agency (EMA) approved new drugs, including each step of the Italian Price and Reimbursement (P&R) process reported in the monthly outcomes of Technical Scientific Committee (CTS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…Lidonnici et al ( 13 ) reported 258 days as average TTM, considering a shorter period than our study (2015-2018) and only including reimbursed drugs (class A and H). In a later publication based on the same data, Raimondo et al ( 15 ), found that TTM increased to 287 days in the 2018-2020 three-year period. Similarly, Prada et al ( 12 , 14 ), only including reimbursed new active substances approved from 2014 to 2019, estimated an average of 228 days and, when focusing on the reimbursed oncological drugs, estimated a time to reimbursement of 248 days.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Lidonnici et al ( 13 ) reported 258 days as average TTM, considering a shorter period than our study (2015-2018) and only including reimbursed drugs (class A and H). In a later publication based on the same data, Raimondo et al ( 15 ), found that TTM increased to 287 days in the 2018-2020 three-year period. Similarly, Prada et al ( 12 , 14 ), only including reimbursed new active substances approved from 2014 to 2019, estimated an average of 228 days and, when focusing on the reimbursed oncological drugs, estimated a time to reimbursement of 248 days.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, it contributes to the existing literature providing an update about the average TTM of drugs in Italy and of the main determinants of AIFA decisions ( 12 , 13 , 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se confrontiamo i risultati di questa analisi con quanto pubblicato negli anni passati con approcci simili ( 9 ), i dati mostrano un sostanziale aumento dei tempi impiegati tra l’apertura CTS e la determina in GU. Questa dilatazione dei tempi si è verificata sia rispetto ai tempi impiegati dalla stessa Commissione nel periodo 2018-2020 (durata media 287 giorni) sia rispetto alla Commissione precedente in carica nel periodo 2015-2018 (durata media 242 giorni vs 341 giorni nell’analisi attuale per l’anno 2022 ( Tabella Supplementare A ) considerando di escludere 118 giorni mediani per apertura CTS per rendere paragonabile questo valore con il medesimo periodo degli anni precedenti pubblicati) ( 9 ). Questo risulta evidente anche nella nostra analisi considerando l’andamento annuo delle tempistiche AIFA su tutte le categorie iniziali.…”
Section: Discussioneunclassified
“…Altri studi a livello nazionale hanno cercato di analizzare le specifiche tempistiche legate all’accesso regionale ( 8 ), alla comparazione tra le Commissioni che hanno gestito la fase di valutazione in periodi differenti ( 9 ) o al potenziale impatto che ha avuto la pandemia di SARS-CoV-2 ( 5 ). A oggi, a nostra conoscenza, poco è stato pubblicato relativamente ai farmaci orfani e alle determinanti delle tempistiche necessarie per l’approvazione e la messa a disposizione di questa particolare categoria di medicinali.…”
Section: Introduzioneunclassified